Abrupt climate change in southeast tropical Africa influenced by Indian monsoon variability and ITCZ migration - Tierney, J. E.; Russell, J. M. (Geophysical Research Letters, 2007)
The timing and magnitude of abrupt climate change in tropical Africa during the last glacial termination remains poorly understood. High-resolution paleolimnological data from Lake Tanganyika, Southeast Africa show that wind-driven seasonal mixing in the lake was reduced during the Younger Dryas, Inter-Allerod Cool Period, Older Dryas, and Heinrich Event 1, suggesting a weakened southwest Indian monsoon and a more southerly position of the Inter-Tropical Convergence Zone over Africa during these intervals. These events in Lake Tanganyika, coeval with millennial and centennial-scale climate shifts in the high latitudes, suggest that changes in ITCZ location and Indian monsoon strength are important components of abrupt global climate change and that their effects are felt south of the equator in Africa. However, we observe additional events in Lake Tanganyika of equal magnitude that are not correlated with high-latitude changes, indicating the potential for abrupt climate change to originate from within tropical systems.
id: 1851; 201ZV Times Cited:4 Cited References Count:31Y